Unintended Consequences : Why Everything You've Been Told About the Economy is Wrong - Conard, Edward (New York Portfolio Penguin, 2012)
Presents a counter intuitive assessment of the financial crisis to identify what the author believes were its actual causes, outlining recommended changes for strengthening the nation's economy.
Include Notes and Index
Keywords: United States -- Economic Conditions -- United States -- Economic Policy -- Finance -- United States -- Economic Policy